Daya Dukung Kawasan Suaka Margasatwa Pulau Semama - Joko Mijiarto; Eva Rachmawati (Jurnal Ilmu Kehutanan, 2023)
The Semama Island Wildlife Sanctuary (SIWS) was part of the Derawan National Tourism Strategic Areas (NTSA) with great potential. As a conservation area, tourism should consider the carrying capacity at SIWS for its optimal development. Therefore, this study aimed to estimate the carrying capacity of the SIWS area using the Physical Carrying Capacity approach. Literature studies, field observations, and interviews were conducted in October 2021 to collect data. The results showed that the pyhsical carrying capacity of the SIWS was 506 people per day, consisting of 45 mangrove tours, 401 snorkeling, and 60 birdwatching activities, indicating the maximum number of visitors the SIWS could accommodate. This information is essential as a consideration for future tourism development.